What shapes attitudes toward paying taxes? Evidence from multicultural european countries - Friedrich G. Schneider; Benno Torgler (Johannes Kepler University of Linz, Department of Economics, 2006)
Considerable evidence suggests that enforcement efforts cannot fully explain the high degree of tax compliance. To resolve this puzzle of tax compliance several researchers have argued that citizens' attitudes toward paying taxes defined as tax morale helps to explain the high degree of tax compliance. However, most studies have treated tax morale as a black box without discussing which factors shape it. Additionally, the tax compliance literature provides little empirical research that investigates attitudes toward paying taxes in Europe. Thus, this paper is unique in its examination of citizen tax morale within three multicultural European countries, Switzerland, Belgium and Spain, a choice that allows far more detailed examination of the impact of culture and institutions using datasets from the World Values Survey and the European Values Survey.
Keywords: 330; Steuermoral; Soziale Werte; Institutionelle Infrastruktur; Vergleich; Schweiz; Belgien; Spanien